2014
DOI: 10.1016/j.bone.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Literature review: The effects of teriparatide therapy at the hip in patients with osteoporosis

Abstract: Teriparatide is a skeletal anabolic treatment for patients with osteoporosis at high risk for fracture. Because adequate clinical trials have not yet been conducted to assess the efficacy of teriparatide for reducing the risk of hip fracture, we review here the literature regarding how treatment with teriparatide affects the hip in patients with osteoporosis. Teriparatide increases cancellous bone volume, improves bone architecture, and - uniquely among osteoporosis treatments - increases cortical thickness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 96 publications
7
46
1
2
Order By: Relevance
“…Nakamura et al [9] also reported that weekly teriparatide administration led to an approximately 2 to 3 % increase in the femoral neck BMD. Adequate clinical trials have not yet been conducted to assess the efficacy of weekly teriparatide for reducing the risk of nonvertebral fractures, but some clinical studies reported that weekly administration of teriparatide increased cortical bone thickness [39][40][41]. However, we were unable to evaluate the effects of these agents on cortical bone in the OVX rats in the present study.…”
Section: Discussioncontrasting
confidence: 62%
“…Nakamura et al [9] also reported that weekly teriparatide administration led to an approximately 2 to 3 % increase in the femoral neck BMD. Adequate clinical trials have not yet been conducted to assess the efficacy of weekly teriparatide for reducing the risk of nonvertebral fractures, but some clinical studies reported that weekly administration of teriparatide increased cortical bone thickness [39][40][41]. However, we were unable to evaluate the effects of these agents on cortical bone in the OVX rats in the present study.…”
Section: Discussioncontrasting
confidence: 62%
“…Parathyroid hormone (PTH) is an 84-amino acid polypeptide that plays an important role in calcium regulation and bone remodeling. Its 34-amino acid analog Teriparatide [90] retains most of the functions of PTH and is an FDA approved drug against osteoporosis. However, being a peptide, it is unstable in body fluids and is readily hydrolyzed by proteinases.…”
Section: Bisphosphonates As Bone-targeting Unitsmentioning
confidence: 99%
“…Due to the relationship between bone ingrowth and osteoblast activity [11], it may be reasonable to activate osteoblast after implantation. Recently, advantages of teriparatide for the treatment of osteoporosis have been acknowledged [12], even comparing with the bisphosphonate, alendronate [13,14]. After THA, teriparatide may be desirable at the point of implant fixation [15] because of its ability to activate osteoblasts to aid osteointegration [11].…”
mentioning
confidence: 99%